Co-inoculation of Borrelia afzelii with tick salivary gland extract influences distribution of immunocompetent cells in the skin and lymph nodes of mice - Severinová, J; Salát, J; Krocová, Z; Reznícková, J; Demová, H; Horká, H; Kopecký, J (Folia microbiologica, 2005)
The impact of Ixodes ricinus salivary gland extract (SGE) on inflammatory changes in the skin and draining lymph nodes of mice, elicited by the infection with the important human pathogen, B. afzelii, was determined using flow cytometry. SGE injected together with spirochetes reduced the numbers of leukocytes and gammadelta-T lymphocytes in infected epidermis at early time-points post infection. In draining lymph nodes, the anti-inflammatory effect of SGE was manifested by the decrease of total cell count compared with that in mice treated with inactivated SGE. Changes in subpopulations of immunocompetent cells apparently reflected the effect of SGE on the proliferation of spirochetes in the host. The significance of tick saliva anti-inflammatory effect for saliva activated transmission of B. afzelii is shown.
Keywords: lymeská nemoc; počet lymfocytů; Animals; Tissue Extracts; Female; slinné žlázy; Lymphocyte Count; Salivary Glands; ženské pohlaví; lymfatické uzliny; Borrelia burgdorferi komplex; Mice; kůže; myši; Borrelia burgdorferi Group; klíšťata; Ticks; Skin; Lyme Disease; podskupiny lymfocytů; Lymph Nodes; tkáňové extrakty; Lymphocyte Subsets; zvířata; Mice, Inbred C57BL; myši inbrední C57BL